2016
DOI: 10.1111/nmo.12784
|View full text |Cite
|
Sign up to set email alerts
|

Colonic response to laxative ingestion as assessed by MRI differs in constipated irritable bowel syndrome compared to functional constipation

Abstract: BackgroundFunctional constipation (FC) and irritable bowel syndrome with constipation (IBS‐C) share many symptoms but underlying mechanisms may be different. We have developed a magnetic resonance imaging (MRI) technique to measure intestinal volumes, transit, and motility in response to a laxative, Moviprep®. We aim to use these biomarkers to study the pathophysiology in IBS‐C and FC.MethodsTwenty‐four FC and 24 IBS‐C were studied. Transit was assessed using the weighted average position score (WAPS) of five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
75
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(85 citation statements)
references
References 28 publications
(84 reference statements)
8
75
0
Order By: Relevance
“…The study by Lam et al . in this issue of the journal identifies three additional physiological measures that are proposed as biomarkers to separate FC from IBS‐C, namely the time to first evacuation, volume of water in the small intestine, and volume of the ascending colon following ingestion of a liter of an osmotic laxative (polyethylene glycol). A novel aspect of the Lam study is that the authors assessed the response to a provocative stimulus (ingestion of an osmotic laxative) rather than attempting to find physiological differences under baseline conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study by Lam et al . in this issue of the journal identifies three additional physiological measures that are proposed as biomarkers to separate FC from IBS‐C, namely the time to first evacuation, volume of water in the small intestine, and volume of the ascending colon following ingestion of a liter of an osmotic laxative (polyethylene glycol). A novel aspect of the Lam study is that the authors assessed the response to a provocative stimulus (ingestion of an osmotic laxative) rather than attempting to find physiological differences under baseline conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Eight studies in Table compared whole gut transit (WGT) in FC vs IBS‐C. The hypothesis was that transit time would be slower in FC than in IBS‐C, and this was found in 3/8 studies . In five other studies there was no statistically significant difference between FC and IBS‐C, even though some of these studies found trends of differences between the groups in the expected direction.…”
Section: Review Of Studies Comparing Ibs‐c To Fcmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the transit in the macrogol period was similar to our previous study where PR oxycodone was administered alone. In a study by Lam et al, 25 the authors used MRI scans to measure intestinal volumes, transit, and motility in response to a single dose of macrogol in patients with either functional constipation or irritable bowel syndrome with constipation. Functional constipation patients showed slower transit and greater ascending colon volumes.…”
Section: Segmental Colorectal Volumesmentioning
confidence: 99%
“…ALTERED COLONIC FUNCTION is a common cause of chronic abdominal pain and often leads to burdensome symptoms. Colonic content and motility are relevant factors when investigating treatments of a number of disorders, such as constipation and irritable bowel syndrome . Knowledge of the distribution of intestinal gas content throughout the gastrointestinal (GI) tract has helped to understand the cause of abdominal symptoms such as bloating and abdominal distension …”
mentioning
confidence: 99%